The effects of perceived price fairness, satisfaction and perceived transaction dissimilarity on customers' behavioral tendencies with regard to the mediating role of trust and the moderating role of trips and familiarity: A case study of the domestic flights at Mehrabad Airport - Mohammad Reza Karimi Alavijeh; Zahra Ghadiri (کاوش‌های مدیریت بازرگانی, 2022)
Introduction: One of the most important management tasks is deciding on selling prices. Given the growing competition among firms and their slow growth in attracting new customers, companies are looking for new ways to boost their sales. Price is also very important as one of the four marketing mixes. The most important point that managers should pay attention to is consumers' perception of fair prices. If consumers find the prices unfair, they show negative reactions. Therefore, a factor influencing the intention of consumers to buy is their perception of price fairness. On the other hand, in recent years, due to rising costs and ticket prices, air travel on short routes has decreased to a rather large extent. In this regard, the main purpose of this study is to show how the perception of price fairness affects behaviors and intentions in airlines. Another purpose of this study is to investigate the mediating roles of the variables of trust, satisfaction and perceived transaction dissimilarity and the moderating roles of familiarity and travel purpose on this relationship.Methodology: This research is applied in terms of purpose and descriptive-survey in terms of data collection and analysis. The measurement tool was a questionnaire. For each of the research variables, a valid questionnaire of previous researches was used. In order to assess the reliability of the questionnaire, Cronbach's alpha test and valid Kolmogorov-Smirnov test were used to test the hypothesis of normal research data. The statistical population included the customers of Mehrabad Airport in Tehran who paid for the ticket themselves. The sample size of this study was 384 people. A structural equation model (SEM) was used to investigate the causal relationships among the variables, and the Amos software served to analyze the data. To express the acceptability of the model, Bentler-Bount standardized fit indices, relative fit, incremental fit, Tucker-Lewis, adaptive indices and full squares were used.Results and Discussion: In this study, the KMO index and the Bartlett test were used to test the adequacy of the sample size, which was confirmed for analysis. With respect to the level of significance and the impact factor, it was found that the perception of price fairness has no significant effect on customer behavioral intentions. On the other hand, the findings showed that, by increased trust, the perception of price fairness can affect the behavioral intensions of customers. It was also shown that this leads to increased customer satisfaction and trust. Moreover, customer satisfaction directly affects customer behavioral intensions and increases brand trust. The other findings of this study showed that Perceived Transaction Dissimilarity both directly and indirectly through the mediation of trust affect customer behavior intensions. Because the effect of fair price perception on customers' behavioral intensions was rejected, Hypotheses 9 and 10, which examined the moderating role of travel purpose and familiarity, were not examined. Therefore, in summary, out of the ten hypotheses of this research, eight were confirmed and two were rejected.Conclusion: According to the results of this study conducted about how perception of fair price affects behavioral intensions through customer satisfaction and trust, it is suggested to airlines to gain customer satisfaction and trust with their pricing strategies so that they can encourage the customers to buy from that brand. Fairness price, especially in Iran and in difficult economic conditions, can determine customer trust and satisfaction, but it can not necessarily affect customer behavior without creating trust and satisfaction alone. Also, according to the findings of this study, the greatest impact on behavioral intensions is through increasing trust, so it is suggested, in the first place, to increase trust in the company in various ways. Perceived Transaction Dissimilarity has been found to have a direct effect on behavioral intensions, so it is suggested as something more tangible and understandable to the customer. The findings also refer to the effect of more than 90% of the perceived difference on the perception of price fairness. In order for the customer to have a higher perception of fairness, airlines should try to increase the Perceived Transaction Dissimilarity from the price increase. One of the limitations of this study is the statistical population that consisted only of passengers of the domestic flights to and from Mehrabad airport who paid for the ticket themselves. It is suggested for future research to study the effect of fair price perception on the behavioral intentions of travelers whose tickets are purchased in their workplace.